PEMODELAN SISTEM PEMBANGKIT LISTRIK HYBRID DIESEL GENERATOR DAN PHOTOVOLTAIC ARRAY MENGGUNAKAN PERANGKAT LUNAK HOMER (Studi Kasus di Pulau Semujur Kabupaten Bangka Tengah) - Dedisukma Dedisukma; Wahri Sunanda; Rika Favoria Gusa (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2015)
Hybrid system is one way in saving the use of petroleum fuels with solar power generating systems apply settlement in Semujur island where it is currently available diesel generator in operation for 3 hours/day with an average power in each house of 178.8 Watt by using a hybrid system modeling software HOMER 3.2.3 the calculation of the cost for the operation the hybrid system. Results of the simulation HOMER that potential energy produced by the photovoltaic array system with lowest solar insolation values on Semujur island amounted to 3.99 kWh/m2/day with renewable fraction in the photovoltaic array system configuration by 34% generating electrical energy by 15515.01 kWh/year with diesel fuel savings of 64.3% of total oil consumption currently operates its own diesel generator spend net present value cost (NPC) Rp 1.143.972.000 and cost of energy (COE) 3,380 Rp/kWh and has advantages sufficient electrical energy for the growth of a population 7 houses in the future.